Identification of Oncogenic Mutations and Gene Fusions in the Follicular Variant of Papillary Thyroid Carcinoma - McFadden, David G. (J Clin Endocrinol Metab, 2014)
BACKGROUND: The diagnosis of the follicular variant of papillary thyroid carcinoma (FVPTC) is increasingly common. Recent studies have suggested that FVPTC is heterogeneous and comprises multiple tumor types with distinct biological behaviors and underlying genetics. OBJECTIVES: The purpose of this work was to identify the prevalence of mutations and gene fusions in known oncogenes in a panel representative of the common spectrum of FVPTC diagnosed at an academic medical center and correlate the clinical and pathological features obtained at the initial diagnosis with the tumor genotype. MATERIALS AND METHODS: We performed SNaPshot genotyping on a panel of 129 FVPTCs of ≥1 cm for 90 point mutations or small deletions in known oncogenes and tumor suppressors and identified gene fusions using an anchored multiplex PCR assay targeting a panel of rearranged oncogenes. RESULTS: We identified a mutation or gene fusion in 70% (89 of 127) of cases. Mutations targeting the RAS family of oncogenes were the most frequently observed class of alterations, present in 36% (46 of 127) of cases, followed by BRAF mutation, present in 30% (38 of 127). We also detected oncogenic rearrangements not previously associated with FVPTC, including TFG-ALK and CREB3L2-PPARγ. BRAF mutation was significantly associated with unencapsulated tumor status. CONCLUSIONS: These data support the hypothesis that FVPTC is composed of distinct biological entities, with one class being identified by BRAF mutation and support the use of clinical genotyping assays that detect a diverse array of rearrangements involving ALK and PPARγ. Additional studies are necessary to identify genetic drivers in the 30% of FVPTCs with no known oncogenic alteration and to better predict behavior in tumors with known genotypes.